2015
DOI: 10.1007/s10592-015-0714-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Bertholletia excelsa populations from the Amazon at different spatial scales

Abstract: Population genetic structure and genetic diversity levels are important issues to understand population dynamics and to guide forest management plans. The Brazil nut tree (Bertholletia excelsa Bonpl.) is an endemic species, widely distributed through Amazonian upland forests and also an important species for the local extractive economy. Our aim was to analyze the genetic structure of Brazil nut trees at both fine and large scales throughout the Amazon Basin, contributing to the knowledge base on this species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
32
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 54 publications
5
32
1
12
Order By: Relevance
“…Cross-pollination (mediated primarily by non-social bees of the genus Xylocopa; Cavalcante et al 2012) is necessary for fruit production and generates high levels of genetic diversity and low levels of inbreeding (Sujii et al 2015). The seeds are contained within a globose, woody fruit (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-pollination (mediated primarily by non-social bees of the genus Xylocopa; Cavalcante et al 2012) is necessary for fruit production and generates high levels of genetic diversity and low levels of inbreeding (Sujii et al 2015). The seeds are contained within a globose, woody fruit (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the ecological, social, and economic importance of the species, a series of studies have examined its production (Kainer et al, 2007;Rockwell et al, 2015), demographics (Wadt et al, 2008;Scoles and Gribel, 2012), silviculture (Kainer et al, 2014;Scoles et al, 2016), and genetics (O'Malley et al, 1988;Sujii et al, 2015;Wadt et al, 2015). Some of these studies express concerns about the impact of intensive seed collection on natural regeneration (Wadt et al, 2008;Scoles and Gribel, 2012) and logging on nut production (Rockwell et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the crowns of fruiting trees are taller than non-productive trees (Scoles et al, 2016), while silvicultural studies have shown that sapling survival and growth is greatest in full daylight conditions, such as forest gaps (Scoles et al, 2011). Population genetic studies based on genetic markers for B. excelsa have been conducted to better understand its genetic structure and diversity, spatial genetic structure (SGS), and inbreeding and mating systems of natural populations, spatially isolated trees in pastures, and trees in plantations (O'Malley et al, 1988;Sujii et al, 2015;Wadt et al, 2015). Such studies have shown lower genetic differentiation between neighboring natural populations (0.018) than spatially distant populations (0.121), significant SGS (Sujii et al, 2015), and varying levels of inbreeding among populations, with some showing no evidence of inbreeding (Sujii et al, 2015;Wadt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As populações de castanhais apresentam diversidade morfológica e fenológica em diferentes regiões da Bacia Amazônica Brasileira, a heterogeneidade na produção, tamanho e massa de frutos e sementes, pode estar relacionada à estrutura genética da espécie sob diferentes escalas espaciais (SUJII et al, 2015). As condições edáficas, climáticas, disponibilidade de água e nutrientes, densidade e composição vegetal influenciam no desenvolvimento saudável da planta e consequentemente na produtividade e plasticidade fenotípica dos castanhais (ZUIDEMA, 2003;KAINER et al, 2007).…”
Section: Introductionunclassified